POAC-Based Character Education Strategies for Fostering Student Discipline and Responsibility - Doris Aviani; Dinny Mardiana (Journal of General Education and Humanities, 2026)
This study aims to analyse character education strategies in improving students’ discipline and responsibility at SMP Al-Falah and SMP Kemah Indonesia 4 in Bandung. Employing a qualitative case study design, the research explores how character education is managed through the functions of planning, organising, actuating, and controlling (POAC). Data were collected through observations, in-depth interviews with principals, teachers, and students, and document analysis. The findings indicate that both schools have implemented character education initiatives oriented toward discipline and responsibility; however, their effectiveness remains limited. Character education planning tends to be general and lacks problem-based strategies; coordination among school actors is inconsistent; implementation relies mainly on routine habituation activities; and supervision emphasises sanctions rather than reinforcement of positive behaviour. These conditions hinder the internalisation of discipline and responsibility as intrinsic values among students. The study highlights the importance of systematic, integrated character education management, emphasising the principal’s role in fostering collaborative practices and balanced supervision to strengthen positive character development in secondary schools.